2008
DOI: 10.1111/j.1365-2559.2008.03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a HER2 scoring system for gastric cancer: results from a validation study

Abstract: IHC/FISH discrepancies were attributed to basolateral membranous immunoreactivity of glandular cells resulting in incomplete membranous reactivity and/or a higher rate of tumour heterogeneity in gastric cancer compared with breast cancer. With modifications to the IHC scoring system, the HercepTest is considered valid for the identification of HER2+ gastric tumours for this clinical trial. Correlation of HER2 scores with clinical outcomes will be needed to determine which patients might benefit from trastuzuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

52
1,024
8
27

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,046 publications
(1,111 citation statements)
references
References 34 publications
(64 reference statements)
52
1,024
8
27
Order By: Relevance
“…Both membranous and cytoplasmic staining was scored as follows: 0, no reactivity or faint staining; 1 þ , faint or weak staining; 2 þ , moderate staining; 3 þ , strong staining in 410% of tumor cells. Membranous alone staining was scored by consensus recommendation on HER2 scoring for gastric carcinoma 30 : 0, no reactivity; 1 þ , faint/barely perceptible membranous reactivity; 2 þ , weak-to-moderate complete or basolateral membranous reactivity; 3 þ , moderate-to-strong complete or basolateral membranous reactivity in 410% of tumor cells. MET overexpression was defined as 2 þ or 3 þ by membranous and cytoplasmic interpretation and only 3 þ by membranous interpretation.…”
Section: Immunohistochemistry For Met Proteinmentioning
confidence: 99%
“…Both membranous and cytoplasmic staining was scored as follows: 0, no reactivity or faint staining; 1 þ , faint or weak staining; 2 þ , moderate staining; 3 þ , strong staining in 410% of tumor cells. Membranous alone staining was scored by consensus recommendation on HER2 scoring for gastric carcinoma 30 : 0, no reactivity; 1 þ , faint/barely perceptible membranous reactivity; 2 þ , weak-to-moderate complete or basolateral membranous reactivity; 3 þ , moderate-to-strong complete or basolateral membranous reactivity in 410% of tumor cells. MET overexpression was defined as 2 þ or 3 þ by membranous and cytoplasmic interpretation and only 3 þ by membranous interpretation.…”
Section: Immunohistochemistry For Met Proteinmentioning
confidence: 99%
“…21,22 Conflicting results are published on heterogeneity of ERBB2 amplification in gastric cancer. [23][24][25] In lung cancer, heterogeneity of HER2 positivity has not been systematically analyzed. This study had the purpose to thoroughly evaluate the possible extent of HER2 heterogeneity in adenocarcinomas, squamous cell carcinomas and large cell undifferentiated carcinomas of the lung.…”
mentioning
confidence: 99%
“…Most studies have been conducted in gastric cancer, which shows ErbB2-positivity rates that vary from 10 to 30%. [1][2][3][4][5] ErbB2 amplification or overexpression also seems to be associated with poorer prognosis, more aggressive disease and shorter survival in gastric cancer. [5][6][7] Preclinical and clinical studies of upper gastrointestinal adenocarcinomas, 2 and in particular, the large ToGA trial, which included adenocarcinomas of the stomach and gastro-oesophageal junction, have demonstrated that trastuzumab exerts antitumour activity on ErbB2-overexpressing tumours.…”
mentioning
confidence: 99%
“…Therefore, for gastric cancer, a modified ErbB2 scoring system for immunohistochemistry has been proposed. 3,10 Data on ErbB2 in oesophageal adenocarcinomas exist to a lesser extent than gastric cancer. The rate of ErbB2 overexpression/amplification in these cancers has been reported at approximately 20-25%, depending on the method of evaluation and the definition used.…”
mentioning
confidence: 99%
See 1 more Smart Citation